Preliminary studies of berberine and its semi-synthetic derivatives as a promising class of multi-target anti-parkinson agents. Issue 12 (18th June 2018) - Ribaudo, Giovanni; Zanforlin, Enrico; Canton, Marcella; Bova, Sergio; Zagotto, Giuseppe
Abstract: Parkinson's disease (PD) is a neurodegenerative disorder bearing motor and nonmotor symptoms. The treatment today is symptomatical rather than preventive or curative and this leaves the field open for the search of both novel molecular targets and drug candidates. Interference with α-synuclein fibrillation, monoamine oxidase (MAO) inhibition, modulation of adenosine receptors and the inhibition of specific phosphodiesterase (PDE) isoforms are some of the currently pursued strategies. We synthesised and studied some semi-synthetic berberine derivatives using a set of in silico tools. We evaluated their drug-likeness and tested the compounds against a set of target proteins involved in the onset or progression of PD, with a particular attention to MAO-B. Preliminary in vitro assay on MAO-B confirmed our in silico predictions. Abstract :